Contingency analysis : a case study of electric power transmission system in Phnom Penh, Cambodia - Sean Piseth; Weerakorn Ongsakul; Nadarajah, Mithulananthan; Wang, Yaw-Juen; France-AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
The successful service to supply electric power is to provide sufficient amount of energy consumption to customers with reliable, security, quality in an economic manner. Contingency analysis is one of the functions in Energy Management System which is in Control Center; this application can be utilized in order to predict what will occur in electric power system followed by the outage of equipment which helps operators to take any actions in advance to maintain the system in the safe condition. Contingency Analysis is very significant application for operation and monitoring of electric power system. This thesis is mainly conducted to contingency analysis by using Artificial Neural Network Approach for IEEE 14 bus system and the existing Phnom Penh electric power transmission system, Cambodia in order to improve system reliability, power quality and security of supply. In this study, it is only focused on power transfer capability in the transmission lines and voltage violation in each bus of the existing system during contingency in this system. The comparison of proposed ANN method, DC Power Flow and AC Power Flow (Newton Raphosn) is made. As a result Artificial Neural obtained the similar results in a fast computation. Finally, the recommendation to reinforce GS3 to CEP line to double circuit line for the existing electric power transmission system to improve the system performance during contingency is also provided
A thesis submitted in partial fulfillment of the requirements for the degree of Mater of Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 2008
Keywords: Electric power transmission -- Cambodia -- Phnom Penh